IMPLEMENTASI PERATURAN DAERAH NOMOR 10 TAHUN 2012 TENTANG PENYELENGGARAAN KESEJAHTERAAN SOSIAL UNTUK MENANGGULANGI KEMISKINAN DI KABUPATEN BEKASI - Yanto Supriyatno; Andi Maulana (Governance, 2022)
The issue of poverty is a problem that has existed for a long time. In the past, in general, people who experienced poverty were not only due to lack of food needs, but poverty took the form of accessibility or minimal material. Through various measures of modern life today, there are still those who do not get educational, health facilities and various things that make it easier for them to be provided. The occurrence of poverty is partly due to the increasing number of workers, but the opportunity to get a job is very limited and the level of income is low in various other activities, the dense population and the higher number of prospective new workers who are still not qualified to do the work, of course. can have an influence on the level of prosperity of the population. The objectives of this research are: 1. Analyzing the implementation of Regional Regulation Number 10 of 2012 concerning the Implementation of Social Welfare to Relieve Poverty in Bekasi Regency 2. Analyzing the achievement of Sustainable Development Goals point 1 (one) through Regional Regulation Number 10 of 2012 concerning the Implementation of Social Welfare in the Regency Bekasi. This study uses a constructivism paradigm with a qualitative research methodology accompanied by a case study approach. The data collection techniques include: observation, in-depth interviews, literature study, and documentation. The results of this study are that the implementation of regional regulations in the implementation of social welfare to reduce poverty has not been implemented according to the rules because there are still many recipients of social assistance who are mistargeted and also the distribution of social assistance is not evenly distributed, socialization about the existence of assistance is still limited, this shows the district government's efforts in seeking social welfare and poverty alleviation has not been serious and systematic.